Alkannin-Induced Oxidative DNA Damage Synergizes With PARP Inhibition to Cause Cancer-Specific Cytotoxicity - Mingxin Chang; Hongge Wang; Jiajing Niu; Yan Song; Zhihua Zou (Frontiers Media S.A., 2020)
Background: Oncogenic transformation is associated with elevated oxidative stress that promotes tumor progression but also renders cancer cells vulnerable to further oxidative insult. Agents that stimulate ROS generation or suppress antioxidant systems can drive oxidative pressure to toxic levels selectively in tumor cells, resulting in oxidative DNA damage to endanger cancer cell survival. However, DNA damage response signaling protects cancer cells by activating DNA repair and genome maintenance mechanisms. In this study, we investigated the synergistic effects of combining the pro-oxidative natural naphthoquinone alkannin with inhibition of DNA repair by PARP inhibitors.Methods and Results: The results showed that sublethal doses of alkannin induced ROS elevation and oxidative DNA damage in colorectal cancer but not normal colon epithelial cells. Blocking DNA repair with the PARP inhibitor olaparib markedly synergized with alkannin to yield synergistic cytotoxicity in colorectal cancer cells at nontoxic doses of both drugs. Synergy between alkannin and olaparib resulted from interrupted repair of alkannin-induced oxidative DNA damage and PARP-trapping, as it was significantly attenuated by NAC or by OGG1 inhibition and the non-trapping PARP inhibitor veliparib did not yield synergism. Mechanistically, the combination of alkannin and olaparib caused intense replication stress and DNA strand breaks in colorectal cancer cells, leading to apoptotic cancer cell death after G2 arrest. Consequently, coadministration of alkannin and olaparib induced significant regression of tumor xenografts in vivo, while each agent alone had no effect.Conclusion: These studies clearly show that combining alkannin and olaparib can result in synergistic cancer cell lethality at nontoxic doses of the drugs. The combination exploits a cancer vulnerability driven by the intrinsic oxidative pressure in most cancer cells and hence provides a promising strategy to develop broad-spectrum anticancer therapeutics.